Two-dimensional polyimide heterojunctions for the efficient removal of environmental pollutants under visible-light irradiation. Issue 31 (25th July 2019) - Wang, Xin; Zhao, Xinyu; Zhao, Yingnan; Tan, Hua-Qiao; Du, Zhilu; Shang, Qingkun; Qiu, Tianyu; Ho, Wingkei
Abstract : Synergism of enhanced light absorption and well intimate interfacial charge transition providing excellent photocatalytic performance of polymide heterojunctions PI–TD x . Abstract : Two-dimensional (2D) heteromaterials with large interface contact and intimate interfacial charge transition have been considered to be an ideal model for constructing highly efficient photocatalysts. However, few studies have reported on these 2D heterojunctions. Herein, we report a series of new 2D heterojunctions comprising polyimide (PI) and perylene-3, 4, 9, 10-tetracarboxylic dianhydride (TD). These heterojunctions, denoted as PI–TD x (where x represents the amount of TD added, i.e., x = 0.13, 0.18, 0.27, 0.54, and 1.08 g), were prepared by the solid thermal copolymerization of melamine (MA), pyromellitic dianhydride (PD), and different amounts of TD. FT-IR spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy analyses were used to verify the 2D heterojunction structure. Photocatalytic experiments reveal that PI–TD x exhibit excellent and stable photocatalytic performance for the degradation of the organic dyes rhodamine B (RhB) and methyl violet (MV), as well as for the photoreduction of Cr(vi ), under visible-light irradiation. Among the samples, PI–TD0.18 exhibits the best photocatalytic performance. Its activity is about 2.7 times and 7.5 times higher than that of individual PIMP (formed by MA and PD) and PIMT (formed by MA and TD) for RhB degradation, respectively. Notably, PI–TD0.18 retains a certain photocatalytic activity under light irradiation at 600 nm. The photocatalytic-mechanism study demonstrates that PI–TD0.18 has a classic type-II heterojunction. Its 2D heterojunction greatly enhances the visible-light absorption of the composites and effectively suppresses the radiation recombination of photogenerated carriers, thereby improving its charge transfer and separation abilities and providing excellent photocatalytic performance. This work may serve as an important reference for the design and construction of new highly efficient 2D organic conjugated-polymer photocatalysts.